Analysis of Technical and Allocative Efficiency Models for Shallot Farming to Increase Production in Karo Regency - Hakim, Tharmizi; Supriana, Tavi; Wibowo, Rulianda P.; Hasanah, Yaya (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The shallot commodity has a strategic role in national food security, but its production still experiences fluctuations, especially in Karo Regency. The primary challenge faced by farmers is the low level of productivity and efficiency in their production. This study aims to analyze the efficiency model of shallot farms in Karo Regency and identify the factors influencing it, including the complex interaction between external factors (climate change), farmers' adaptive responses, and existing socioeconomic structures. The methods employed are a combination of qualitative and quantitative approaches, including surveys and in-depth interviews. Data analysis will use the Stochastic Frontier Analysis (SFA), Data Envelopment Analysis (DEA), and Tobit regression models. The expected results can provide a comprehensive understanding of the sustainability of shallot farming and offer integrated policy recommendations for local governments, extension workers, and farmers.